Design and Management of Sustainable Built Environments - Yao, Runming (Springer London : Imprint: Springer, 2013)
Climate change is believed to be a great challenge to built environment professionals in design and management. An integrated approach in delivering a sustainable built environment is desired by the built environment professional institutions. The aim of this book is to provide an advanced understanding of the key subjects required for the design and management of modern built environments to meet carbon emission reduction targets. In Design and Management of Sustainable Built Environments, an international group of experts provide comprehensive and the most up-to-date knowledge, covering sustainable urban and building design, management and assessment. The best practice case studies of the implementation of sustainable technology and management from the BRE Innovation Park are included. Design and Management of Sustainable Built Environments will be of interest to urban and building designers, environmental engineers, and building performance assessors.  It will be particularly useful as a reference book for undergraduate and postgraduate students in the built environment field. .